Analisis Spektra UV-Visible Senyawa Bahan Alam Tersensitasi Zat Warna: Pengembangan Modul Praktikum Kimia Komputasi - Ni Kadek Mai Sasmita Wardani; Jeckson Siahaan; Rahmawati Rahmawati; Saprizal Hadisaputra (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2022)
The research aims to examine the validity, practicality, and effectiveness of the computation chemistry laboratory works module to analyze spectra UV-Visible of natural compounds in dye-sensitized solar cells. The research design is 4D (Define, Design, Development, and Dissemination). The population is 80 students in the Chemistry Education Study Program, The Faculty of Teacher Training and Education Studi, the University of Mataram Indonesia, who have completed the computation chemistry course. The sample in this research is 20 students taking to be respondents for the computation chemistry laboratory practical works module with a random sampling technique. The validity value studied by Aiken V of the laboratory module is V= 0,90 with the reliability R=0,98. It means the laboratory module has a highly valid category to be applied. The value of the practicality module gained from the students' responses is with average practicality of 91%. It means the module has a highly practical category. The module's effectiveness could be seen from the students' point with an average of 83.5, which shows that the module has a high effectiveness category. In conclusion, the computation chemistry laboratory works module that is being developed is highly valid, practical, and effective to be applied.